P-356 Clinical implications of first-trimester ultrasound dating in singleton pregnancies obtained through in vitro fertilization. (30th June 2022) - Dallagiovanna, C; Reschini, M; Somigliana, E; Rapisarda, A; Boito, S; Pezone, M.G; Accurti, V; Ferrara, G; Persico, N
Abstract: Study question: Is there a correspondence between ultrasound estimation of gestational age (GAUS ) and its calculation based on embryo transfer date (GAIVF ), in in-vitro fertilization (IVF) pregnancies? Summary answer: GAUS and GAIVF are not overlapping, being the first mildly greater than the latter, maybe due to anticipated ovulation and fertilization or accelerated embryo development. What is known already: In IVF pregnancies the precise date of conception is known. However, it is possible that some factors (such as a time delay between conception and implantation, an early in-vitro embryo development, and the maternal environment itself with its altered hormonal milieu) may influence the early stages of embryonic development. Data regarding first-trimester fetal development in IVF pregnancies are in fact conflicting and both underestimation and overestimation of the true GA were reported when traditional charts were used for ultrasound pregnancy dating. Study design, size, duration: A retrospective study was performed, including all singleton IVF pregnancies who underwent the first-trimester ultrasound scan for the screening of aneuploidies between January 2014 and June 2019. For each pregnancy GA was determined using two alternative methods: one based on the date of embryo transfer (GAIVF ), and one based on ultrasound measurement of crown-rump length (CRL) (GAUS ). GA were compared to search for any discrepancy. The impact of pregnancy dating on obstetric outcome was evaluated. Participants/materials, setting, methods: All women with singleton pregnancies conceived by conventional IVF or intracytoplasmic sperm injection (ICSI), who performed first-trimester ultrasound scan for the screening of aneuploidies at the Department of Obstetrics and Gynecology 'L. Mangiagalli', Fondazione IRCCS Ca' Granda Ospedale Maggiore Policlinico, were included. Exclusion criteria were as follows: multiple pregnancy (i.e., the evidence of more than one gestational sac at the first ultrasound scan), abnormal karyotype and/or congenital malformations detected either in pre- or postnatal period. Main results and the role of chance: Overall, 249 women were selected: 111 pregnancies (45%) by conventional IVF, and 138 (55%) by ICSI. Among the included women, 127 (51%) pregnancies resulted from frozen-thawed embryo transfer. At first trimester ultrasound scan, the discrepancy in days between GAUS and GAIVF was ≥ 4 days in 32 cases (13%, 95%CI: 9-18%). It ranged within 2 and 3 days in 100 cases (40%, 95%CI: 34-47%). In 117 cases (47%, 95%CI: 41-53%) GAUS and GAIVF overlapped or showed a discrepancy of ± 1 day. Comparing GAUS and GAIVF at first trimester ultrasound scan, the median values of GA were 88 [86 - 91] days and 87 [85 - 90] days, respectively (p < 0.001). The median difference was 1 [0 - 2] days, with GAUS systematically higher than GAIVF . This discrepancy persisted when subgroups were analyzed comparing different IVF procedures (conventional IVF versus ICSI, cleavage versus blastocyst transfer, frozen versus fresh transfer). The overall duration of pregnancy differed, with median values of 274 [269 - 281] days in GAUS group and 273 [268 - 280] days in GAIVF group, (p > 0.001). No impact of the dating method on obstetric outcomes was observed, being no differences in the rate of preterm birth or abnormal fetal growth. Limitations, reasons for caution: This is a retrospective study and thus exposed to the inaccuracies of this study design. Moreover, being a single-centre study, the sample size is relatively small. Finally, ultrasound evaluations were performed by multiple operators: although they are all certified, there is some inter-individual variability that may impact on the results. Wider implications of the findings: Despite a known date of conception, it is difficult to assume that the oocyte retrieval date precisely resembles the date of natural ovulation and conception. IVF seems to anticipate fertilization. On these bases, it would be advisable to date IVF pregnancies using GAUS to realign them to natural pregnancies. Trial registration number: Not Applicable